2023
DOI: 10.1177/03635465221135770
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Decellularized Tendon-Derived Stem Cell Sheet for Promoting Graft Healing After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Stem cell sheets provide a scaffold-free option for the promotion of graft healing after anterior cruciate ligament reconstruction (ACLR). However, cell viability, stability, and potential uncontrolled actions create challenges for clinical translation. The decellularization of cell sheets may overcome these problems as studies have shown that the natural extracellular matrix of stem cells is bioactive and can promote tissue repair. Hypothesis: The decellularized tendon-derived stem cell (dTDSC) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Third, it is unclear whether the improved repair efficacy of cell sheets is primarily the result of viable cells or the ECM within the sheets. Recently, Yao et al 28 evaluated the repair effect of decellularized tendon–derived stem cell sheets and found that they could promote graft healing after anterior cruciate ligament reconstruction. We could conclude from the current study that the ECM of the cell sheets promoted tendon-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is unclear whether the improved repair efficacy of cell sheets is primarily the result of viable cells or the ECM within the sheets. Recently, Yao et al 28 evaluated the repair effect of decellularized tendon–derived stem cell sheets and found that they could promote graft healing after anterior cruciate ligament reconstruction. We could conclude from the current study that the ECM of the cell sheets promoted tendon-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Removing cellular immunogenicity from the cell sheet may be a Frontiers in Bioengineering and Biotechnology frontiersin.org better option, indicating that the cell sheet can be applied to largescale applications rather than personalized customization. In further research, Pauline Po Yee Lui et al (Shang et al, 2023) chose to decellularize the TDSCs-formed cell sheet, and found that the decellularized cell sheet also promoted graft healing, tunnel bone formation, and angiogenesis (Yao et al, 2023). Hence, the extracellular matrix in the cell sheet may play a pivotal role in promoting healing.…”
Section: Scaffoldsmentioning
confidence: 99%
“…Moreover, different types of C-dECMs have been verified for their capacity to induce osteogenic differentiation of re-seeded BMSCs, including cell sheets derived from bone marrow mesenchymal stem cells (BMSCs), MC3T3 osteoblasts, and L929 fibroblasts [ 22 ]. In addition, C-dECM showed good effect in ligament regeneration: stem cell sheets-derived dECM provide an ectogenic scaffold-free option, enhancing bone formation and angiogenesis by BMP-2 and VEGF, modulating macrophage polarization and MMP/TIMP expression, and physically promoting ligament reconstruction [ 55 ]. In addition, many techniques have been used to construct C-dECM in vitro; for example, studies showed that the addition of a certain amount of ascorbic acid to the culture medium promoted ECM deposition and the formation of cell membranes [ 56 ].…”
Section: Application Of Decm Of Different Forms In Periodontal Regene...mentioning
confidence: 99%
“…The fabrication and in vitro analysis of dECM (solid dECM and soluble dECM) of various tissue origins are prerequisites for applications. The dECM can be generated and improved by a variety of methods, and complex periodontal regeneration modules based on the dECM were recently developed [ 20 , 48 , 55 , 87 ].…”
Section: Summary and Prospectsmentioning
confidence: 99%